WEBINAR ANTI BULLYING UNTUK MENINGKATKAN KESADARAN MENGENAI BAHAYA DAN CARA UNTUK MENGHADAPI BULLYING - Siska Oktari; Sabrina Puti Afifah; Nazri Sakinah; Sheila Maeshade; Jessica Berliana (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effectiveness of psychoeducation on dangers and how to deal with bullying through the